Study on Test‐Mass Charging for Taiji Gravitational Wave Observatory - Ruilong Han; Minghui Cai; Tao Yang; Liangliang Xu; Qing Xia; Xinyu Jia; Dawei Gao; Mengyao Li; Longlong Zhang; Hongwei Li; Jianwei Han (Space Weather)
Abstract Taiji is proposed as a space‐based gravitational wave (GW) observatory consisting of three spacecraft in a heliocentric orbit meanwhile with the distance of 3 million kilometers ahead of the Earth at about 20°. Free‐falling test masses (TMs) are a key component of the interferometer for space‐based GW detection in the 0.1mHz–1 Hz frequency range. Exposure to energetic particles in the space environment can lead to charging of the TMs and thus cause additional electrostatic forces and Lorentz forces that limit the sensitivity of the interferometer and may affect the quality of the scientific data. This study aims to model the charging of TMs during Galactic cosmic rays and solar proton events (SPEs) using the Monte Carlo simulation toolkit meanwhile with constructing the sophisticated 3D spacecraft. The results show that the total net charging rates are 34.48 +e/s and 33.85 +e/s on TM1 and TM2 during the solar minimum, and 9.58 +e/s on TM1 and 9.65 +e/s on TM2 during the solar maximum. We confirm that no matter for solar minimum or solar maximum, protons contribute to the largest proportion of the TMs charging rate. Furthermore, charging for five typical SPEs is also investigated, and the maximum TMs charging rate reaches 76,674 +e/s, indicating that sporadic SPEs have a high risk for TMs charging. Finally, the charging rates of a TM imitation are tested on ground by the 30–50 MeV proton irradiation experiment, and the experimental results show good consistence with the simulation results with the error <10%.